A new Muslim order the Shia and the Middle East sectarian crisis - Pelham, Nicolas (I.B. Tauris, 2008)
Nicolas Pelham explores how America's overthrow of the Baath party in Iraq, and the failures of Washington's post-invasion regime spawned a Shiite revolution in the heartland of the Arab world. Through first-hand accounts beginning with Saddam's rule to the post-Bremer period, he traces the turning of the tables from a Sunni to Shia-led state. Pelham recounts how Shia clerics led the largest protest the region had seen since the Iranian Revolution to topple Paul Bremer, America's head of the Coalition Provisional Authority in Iraq. As Washington struggled to control the situation, Pelham reveals how the Ayatollahs' drive for elections won power for their acolytes to draft the constitution for a utopian Shia state.